2004
DOI: 10.2337/diabetes.53.8.2164
|View full text |Cite
|
Sign up to set email alerts
|

Severe Persistent Hyperinsulinemic Hypoglycemia due to a De Novo Glucokinase Mutation

Abstract: Glucokinase (GK) is a glycolytic key enzyme that functions as a glucose sensor in the pancreatic ␤-cell, where it governs glucose-stimulated insulin secretion (GSIS). Heterozygous inactivating mutations in the glucokinase gene (GCK) cause a mild form of diabetes (maturityonset diabetes of the young [MODY]2), and activating mutations have been associated with a mild form of familial hyperinsulinemic hypoglycemia. We describe the first case of severe persistent hyperinsulinemic hypoglycemia due to a "de novo" mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
155
1
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(171 citation statements)
references
References 21 publications
8
155
1
7
Order By: Relevance
“…Similarly, it has been shown that glucokinase plays a critical role in restoring beta cell mass following acute beta cell loss triggered by transgenic manipulation [27]. Clinically, it has been observed that a gain-of-function glucokinase mutation results in enlarged islets [7,10]. These findings support a hypothesis that chronic treatment with a GKA may help to preserve beta cell mass in patients with type 2 diabetes, and thereby provide a more durable form of antihyperglycaemic action.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similarly, it has been shown that glucokinase plays a critical role in restoring beta cell mass following acute beta cell loss triggered by transgenic manipulation [27]. Clinically, it has been observed that a gain-of-function glucokinase mutation results in enlarged islets [7,10]. These findings support a hypothesis that chronic treatment with a GKA may help to preserve beta cell mass in patients with type 2 diabetes, and thereby provide a more durable form of antihyperglycaemic action.…”
Section: Discussionsupporting
confidence: 74%
“…There is considerable interest in the development of GKAs as potential therapies for type 2 diabetes because glucokinase activity plays an essential role in glucose-sensing by beta cells and glucose metabolism by hepatocytes [2][3][4][5]. The importance of this enzyme in glucose homeostasis was first widely recognised with the discovery of clinical syndromes resulting from loss-of-function and gain-of-function glucokinase gene mutations [6][7][8][9][10]. The gain-of-function mutations produce dominant/recessive clinical phenotypes of hyperinsulinaemic hypoglycaemia and are of particular pharmacological interest because they alter glucokinase function in a manner closely related to GKA action [11].…”
Section: Introductionmentioning
confidence: 99%
“…Loss of both GK alleles results in permanent neonatal diabetes, whereas heterozygous inactivating mutations of GK lead to maturity-onset diabetes of the young (MODY2; Hattersley et al 1992). Conversely, rare activating mutations of GK result in hyperinsulinaemic hypoglycaemia (Glaser et al 1998, Christesen et al 2002, Gloyn et al 2003, Cuesta-Munoz et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…A ativação dessa enzima aumenta a oxidação de glutamato e aumenta a relação ATP/ADP na célula B. As mutações ativadoras de GCK (7p15-p13) reduzem o limite da secreção de insulina estimulada pela glicose (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41).…”
Section: Glud1 E Gckunclassified